2016
DOI: 10.1136/bcr-2015-213585
|View full text |Cite
|
Sign up to set email alerts
|

Erythema induratum of Bazin and Ponçet's arthropathy as epiphenomena of hepatic tuberculosis

Abstract: A 42-year-old black woman presented with fever, polyarthritis, livedo reticularis, subcutaneous calf nodules and hepatomegaly. She had been diagnosed with depression 6 weeks prior. Blood analysis showed anaemia, elevated erythrocyte sedimentation rate and C reactive protein, elevated liver enzymes, and positive antinuclear and antiribonucleoprotein antibodies. Abdominal ultrasound revealed heterogeneous hepatomegaly with necrotic lymphadenopathy around the caeliac trunk and splenic hilum. We considered the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…24 The diagnosis of PD, when presented with history of watery diarrhea and symmetrical multiple joint (including small joints of hand) arthritis, may be difficult and requires careful exclusion of reactive and rheumatoid arthritis. 25 Paediatric cases are another underrepresented groups with few reports. In a large case pool of 462 cases of pediatric rheumatologic disorders from South Africa, only four cases of PD were described.…”
Section: Clinical Presentationsmentioning
confidence: 99%
“…24 The diagnosis of PD, when presented with history of watery diarrhea and symmetrical multiple joint (including small joints of hand) arthritis, may be difficult and requires careful exclusion of reactive and rheumatoid arthritis. 25 Paediatric cases are another underrepresented groups with few reports. In a large case pool of 462 cases of pediatric rheumatologic disorders from South Africa, only four cases of PD were described.…”
Section: Clinical Presentationsmentioning
confidence: 99%
“…Early response to ATT was seen in this case within 1 week of initiating ATT, whereas most studies showed response in 3–4 weeks after starting ATT. [ 1 5 ]…”
mentioning
confidence: 99%